INFLUENCE OF DIDACTIC CONDITIONS ON EFFECTIVENESS OF FORMATION AT YOUNGER SCHOOL STUDENTS OF INFORMATIVE UNIVERSAL EDUCATIONAL ACTIONS OF STATEMENT AND A SOLUTION - Alekseeva, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents methodological, diagnostic and technological (procedural) components of the formation in younger schoolchildren of cognitive universal educational actions (PAP) of the setting and solution of the problem. The methodology of forming the components of «problem setting» and «problem solving» is disclosed in the article from the perspective of the system approach. The diagnostic component presents the diagnostic tactics (criteria, indicators, model of formation levels) of the PDS «problem setting» and «problem solving» in younger schoolchildren; There is provided didactic-methodical instrumentation for determining possible levels of UDM formation, problem setting and problem solution at the control stage of the experiment (qualitative and quantitative analysis of the execution of complex diagnostic tasks by junior students). The procedural component shows that compliance in the educational activity of the primary school with the principles of technology of intellectual and developing education, provision of visualization of problem situations, implementation of speech control of the process of setting and solving the problem through the development of speech logic in children increases the efficiency of the process of formation of education of students of the primary school in the younger schoolchildren in the ability to formulate and solve problems.The study carried out and the analysis of its results make it possible to draw a conclusion on the expediency of implementing in the educational activity of the primary school a designated didactic strategy, which helps the teacher to master the universal didactic tools of teaching younger schoolchildren to solve the educational problem and solve it.